The comparative analysis of FMCG enterprises' vision, mission, and core values focusing on strategic human resources - Samia Shanjabin; Amanta Hasnat Oyshi (International Journal of Financial, Accounting, and Management, 2021)
Purpose: This study focused on a comparative analysis of the FMCG enterprises' vision, mission, and core values focusing on strategic human resources. Research methodology: This study is qualitative, and altogether twenty-three FMCG company's websites have been used for analyzing the company's mission, vision, and core values. Results: Among the twenty-three companies, only seven (Bombay Sweets and Co. Ltd., Arla, Akij Group, Ispahani Foods Limited, Golden Harvest Agro Industries Limited, Walton Group, and City Group) have no focus on strategic human resources in their mission, vision and core values. Sixteen companies have a concern about strategic human resources in vision, mission, and core values. Limitations: This study only includes results from the FMCG of Bangladesh rather than including other industries like telecommunication, MNCs, and other areas. Again, this study is limited by including only a few FMCGs. Contribution: This study results contribute to strategic human focus in the vision, mission, and core values of FMCG enterprises of Bangladesh through a comparative analysis also emphasizes strategic human focus in the employees' development.